ANALISIS PENGAMBILAN KEPUTUSAN DALAM KENDALA DI UMKM WARUNG SEBLAK TEH ROS - Purnamasari, Regina; Nehamia Yuniati Aritonang; Muhammad Syahid Alghifari; Ujang Suherman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the economy; however, in practice they often face managerial challenges, particularly in decision-making processes. This study aims to analyze decision-making constraints in the MSME Warung Seblak Teh Ros, focusing on labor management, capital management, raw material management, and marketing. This research uses a qualitative descriptive method with an observational approach. Data were collected through direct observation, interviews with the business owner, and supporting documentation. The results indicate that decision-making at Warung Seblak Teh Ros is still simple and intuitive, yet sufficiently effective in maintaining business sustainability. The main constraints identified include limited labor, the absence of structured financial records, fluctuating raw material prices, and limited marketing strategies. Nevertheless, adaptive decisions made by the business owner have had a positive impact on the increase in the number of customers throughout 2024. The study concludes that the quality of managerial decision-making, even when applied in a simple manner, plays a crucial role in supporting MSME sustainability. This research is expected to serve as a reference for MSME actors in improving the effectiveness of business decision-making.